Path to a Peaceful Death: Coping with Terminal Illness - Khumukcham Anupama Devi; Thokchom Soniya Devi; Sudhakar Kumar Singh (International Journal of Medical Research and Review, 2024)
Terminal illness can cause immense suffering, both physical and emotional, for patients and their families. However, with appropriate care and support, patients can experience a peaceful death. This article reviews the literature on peaceful death from terminal illness, including the psychological, emotional, and physical factors that contribute to a peaceful death. The article highlights the importance of early palliative care and psychological interventions in improving the quality of life and reducing suffering for patients with terminal illness. The role of emotional support and legacy-making in enhancing well-being for patients are also discussed. The article concludes by stressing the need for continued efforts to improve end-of-life care for patients with terminal illness.